The Arabian Nights (Vol.2) : More Marvels and Wonders of the Thousand and one nights - Adapted by Zipes, Jack, 1937- (New York Signet Classics, 2010)
Volume Two in a collection of tales representing distinctive genres--from fairy tales to erotica--reveals the customs and societies in the medieval Middle East, as told by the mythic Sheherazade. Includes a new Introduction.
Keywords: Arab countries -- Arabs -- Folklore